Assessment of the Implementation of Special Program in Journalism (SPJ): Basis for an Intervention Program - Tura, Ryan (Journal of Interdisciplinary Perspectives, 2025)
In light of the implementation of the Special Program in Journalism (SPJ) and the low performance of the school in school’s press conference competitions, the study aims to assess the level of standard, performance, and challenges in implementing the SPJ program through the lens of student journalists as a basis for an intervention program. The study consists of one hundred (100) journalist respondents purposively selected through purposive sampling. The study used a mixed method research design using sequential explanatory methods, which employ survey questionnaires and polyangulation, which consist of interviews and Focus Group Discussion (FGD) as tools for data gathering. The survey questionnaires were adopted from existing studies and underwent validation and reliability testing. The study used semi- structured questions for the interview questions to allow the respondents to respond extensively. To analyze and interpret the quantitative data, the study used descriptive statistics using weighted mean, while for qualitative, the study adopted Colaizzi's 1978 method of data analysis, which involves steps such as transcribing significant statements into meaning units and extracting emerging themes. The study found that the level of standard and performance and outcomes in implementing a Special Program in Journalism (SPJ) in school is satisfactory. Meanwhile, themes such as a lack of facility, uniformity of instruction, disengagement in the training, and lack of parental support emerged as challenges in the implementation of the program. The study concludes that implementing the SPJ program fosters challenges like lack of facility, student disengagement among journalists, and uniformity of instruction, which constitutes a low level of performance and standards; thus, an intervention program is recommended.